Freud and Jung on religion - Palmer, Michael (Routledge, 1997)
""CONTENTS""; ""FOREWORD""; ""Part I SIGMUND FREUD: PSYCHOANALYSIS AND RELIGION""; ""1 INTRODUCTION""; ""2 TOTEM AND TABOO""; ""3 RELIGION AND ILLUSION""; ""4 FORMS OF RELIGIOUS NEUROSIS""; ""5 A CRITICAL APPRAISAL""; ""Part II CARL GUSTAV JUNG: ANALYTICAL PSYCHOLOGY AND RELIGION""; ""6 INTRODUCTION""; ""7 THE STRUCTURE OF THE PSYCHE""; ""8 GOD AS ARCHETYPE OF THE COLLECTIVE UNCONSCIOUS""; ""9 GOD AND INDIVIDUATION""; ""10 A CRITICAL APPRAISAL""; ""NOTES""; ""BIBLIOGRAPHY""; ""INDEX OF NAMES""; ""INDEX OF SUBJECTS: FREUD""; ""INDEX OF SUBJECTS: JUNG""